INVESTIGATION OF THE SORPTION CHARACTERISTICS OF ACTIVATED CARBONS - A.E. Ilyassov; A.О. Baikonurova; B.N. Surimbayev (Academic Scientific Journal of Chemistry, 2021)
The article presents the results of a comparison of the sorption characteristics for gold of crushed activated carbon of the foreign Haycarb brand, obtained from expensive raw materials - coconut shells, and crushed activated carbon of the domestic Shubarkol brand, obtained from relatively cheap raw materials - low-ash coking coal. The activated carbon Shubarkol crushed to a class of -3.6+1.0 mm, was produced in Kazakhstan from coking coal by Shubarkolkomir JSC. To test the crushed coal Shubarkol, industrial crushed coal Haycarb, made from coconut shells, was used as a reference sample. This coal is widely used in gold mining enterprises for the sorption of dissolved gold from cyanide solutions and pulps. For research, a productive solution of the process of heap leaching of gold from oxidized ore of one of the deposits of Kazakhstan was used with the composition, mg/L: gold 0.82; silver 0.44; copper 8.34; pH 11.05. Determination of the sorption characteristics of coals was carried out by the method of saturation with gold when changing solutions. The results of changes in the gold content in the mother solution, its extraction and saturation of coals with precious metal after each sorption cycle from the productive heap leaching solution using crushed coals of the Shubarkol and Haycarb brands are presented. It follows from the obtained data that Shubarkol activated carbon has similar sorption characteristics compared to Haycarb activated carbon. The working capacity for gold of Shubarkol coal was 2.28 kg/ton of sorbent, and of Haycarb coal - 2.57 kg/ton. Thus, crushed coal Shubarkol, obtained from relatively cheap raw materials, can be successfully used at industrial facilities instead of foreign sorbent